European Football Championship 2020/2021: Analysis of goals scored and evaluation of statistically parameters in matches - Zivanovic, V. (Sport Science & Practice, 2022)
The aim of the study was to analyse the characteristics of goals scored in the tournament in terms of a specific way of evaluation. Based on a sample of 51 matches and the participation of 24 national teams, this study is based on the personal observation of the researcher, that is, the analysis was based on watching the matches live via domestic cable channels, as well as on the UEFA official YouTube channel. A two-way analysis of variance between groups was used to process one part of the data. A total of 142 goals were scored. The fixed factor showed the highest prevalence of goals scored in the period of 45-60 minutes (30), while the fixed factors included the types of attacks and the number of goals scored: (80) continuous attacks (mean value = 53.7 minutes), (13) fast attacks (59.5 minutes), (14) counter-attacks (55.7 minutes) and (35) set plays or interruptions (51.8 minutes). One final touch was evaluated (80 or 65.6%), as well as two touches (17 or 13.9%). The highest number of hits (37) was achieved with the inside of the foot (mean value = 53.5 minutes) compared to (27) when hitting the ball with the header (54.4 minutes) and (21) when kicking the ball with the middle part of the foot ridge (49.5 minutes). Most goals were scored with the right foot (66 or 46.5 %), i.e. (90) goals were scored within sixteen meters (outside the box) (54.1 minutes). The first goal provided value (33 or 64.7 %) of the final victory in the match. The obtained results point out to the coaches that they should focus on quick attacks and counter-attacks that consequently lead to scoring goals. Attention must also be paid to more ball strikes with the outside of the foot and the outside part of the foot ridge.